FENOMENA PACARAN BERBEDA AGAMA DI KALANGAN PEMUDA-PEMUDI KOTA DENPASAR - Selarani, Katrin; Punia, I Nengah; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The phenomenon of different dating religious in the city of Denpasar can be analyzed through the study of sociology. This research try to discuss and explain about the conflicts faced by young couples who dating different religions. This research uses explorative qualitative research method with analysis of conflict theory by Lewis Alfred Coser which divides conflict into two parts. First, realistic conflict is direct conflict, while second non-realistic conflict is indirect conflict, besides those two conflicts, Lewis A. Coser also discusses the theory of safety valve. Based on the results of this study, it is known that the conflict faced by couples who dating different religions can be overcome by way of communication and respect each other. Keywords: Dating, different religions, young people, Denpasar.